Event-Based Supply Chain Network Modeling: Blockchain for Good Coffee - Bager, Simon L.; Düdder, Boris; Henglein, Fritz; Hébert, Juan Manuel; Wu, Haiqin (Frontiers in Blockchain, 2022)
Blockchain provides the potential for a secured decentralized information infrastructure for efficient value chains and effective horizontal integration across institutional boundaries. It offers a multitude of innovative ways to handle transactional data in a decentralized fashion. Supply chain management has been a prominent blockchain application due to the trust and immutability provided by a blockchain. Blockchain-as-a-Service could enable secure value transfer and transparent governance of complex supply chains, such as premium and sustainable commodities like certified or specialty coffee. We present REALISTIC, a modeling framework for supply chain networks that includes production processes. It is built on McCarty's Resources-Events-Agents (REA) accounting model and is extended with secure transformations, which guarantees that physical resources can be consumed and produced but cannot directly or indirectly lead to resources being produced out of thin air. We present a case study for an event-based blockchain solution for end-customers in an end-to-end commodity supply chain. The model handles product provenance, transparency, sustainability and quality information, production, transportation, and certification standards across the coffee supply chain. The model is based on an existing coffee supply chain involving farmers in Colombia through cooperatives, processors, traders, importers, and a Scandinavian roasting company. Its REALISTIC-based analysis is the foundation for the design and prototypical implementation of a decentralized supply chain network proxy for validation. Its source code is made available on GitHub. Overall, the development process allows insights into the iterative co-design of general blockchain solutions for sustainable commodity supply chains. Our fully implemented open-source prototype validates the practicability of the event-based supply chain network modeling in field tests. We find that REALISTIC modeling for event-based systems using iterative co-design is a promising approach for the development of complex supply chain applications.